Tiktok sebagai Agen Jurnalistik Dakwah Masa Kini: Studi Deskriptif pada Akun Tiktok @Ajiepanqestu - Erwan Efendi; Fadilah Khairunnisa Rangkuti; Tamanda Siregar (VISA: Journal of Vision and Ideas, 2024)
Social media affects people of all ages and in all groups in this technologically advanced society. One of the media platforms used in preaching is TikTok. Researchers employ a qualitative approach using a descriptive methodology. The purpose of this study was to evaluate Tiktok's effectiveness as a da'wah platform. The sample used spans two weeks, from October 1, 2023, to October 14, 2023, and is content from the TikTok accounts @ajiepanqestu. The study's findings, which are based on how many people view and like the TikTok accounts @ajiepanqestu consistently FYP, should help spread the word about da'wah more effectively and efficiently.